One-step co-culture fermentation strategy to produce high-content fructo-oligosaccharides. (1st December 2018) - Nobre, C.; Gonçalves, D.A.; Teixeira, J.A.; Rodrigues, L.R.
Graphical abstract: Highlights: Co-culture Aspergillus ibericus / Saccharomyces cerevisiae increases FOS yield/purity. Temperature, pH, yeast extract and aeration significantly affects FOS yield/purity. Simultaneous inoculation led to mixtures up to 97.4% of pure FOS. Bioreactor fermentations yielded 0.70 gFOS .gin.GF –1 with 133.7 g L −1 FOS content. One-step fermentation of 45 h lead to high-content FOS mixtures with high-purity. Abstract: An integrated process enabling the simultaneous production and purification of fructo-oligosaccharides (FOS) was explored. A co-culture fermentation with Aspergillus ibericus (used as FOS producer strain) and Saccharomyces cerevisiae YIL162 W (for small saccharides removal) was optimized. Inoculation conditions of S. cerevisiae, fermentative broth composition, temperature and pH were optimized by experimental design. Yeast extract concentration and temperature were the most significant variables affecting FOS purity. Co-culture fermentations with simultaneously inoculation of the strains, run under 30 °C, initial pH 6.0 and 17 g L –1 yeast extract led to FOS mixtures with 97.4 ± 0.2% (w/w) purity. The fermentations conducted in bioreactor, at a 0.8 vvm aeration rate, yielded 0.70 ± 0.00 gFOS .ginitial GF –1 at 45 h fermentation, with a FOS content of 133.7 ± 0.1 g L −1 . A purity of FOS up to 93.8 ± 0.7% (w/w) was achieved. The one-step fermentation proved to be efficient, economical and fast.